Awareness and Perceptions of University Students in the Business College towards Energy Savings and Renewable Energy Sources in Saudi Arabia - Akinwale, Yusuf Opeyemi (International Journal of Energy Economics and Policy, 2022)
Achieving sustainable development goals and realizing the goal of Kyoto Protocol, Paris Agreement and Glasglow Climate Pact to keep the world temperature rise lower than 2o C above pre-industrial levels, there is a need to engage some of the stakeholders who are part of the energy users in a society. Majority of the Saudi citizens are youths and a large number of them are still undergoing university education. This study assessed the awareness, perception and attitudes of university students in the college of business towards energy savings and renewable energy (RE) in the Eastern province of Saudi Arabia. The results using descriptive analysis revealed that the level of awareness of students about energy savings and renewable energy is at medium level. While few of them are concerned about energy-savings and RE usage, many of them are indifferent, which could be as a result of their poor knowledge and awareness about it. At least 3 out of 5 students believed that fossil fuels have negative impact on the environment. Furthermore, the results of logistic regression indicate that there is no statistical difference between gender, age and awareness of energy savings and RE. More so, the results also show that energy education and family factors are statistically significant in influencing students’ awareness of energy savings and RE. Appropriate government policy in university academic curriculum which incorporates energy savings and renewable energy education is recommended in order to realize the government Vision 2030 which is also in line with the UN Climate goal.